2014
DOI: 10.1177/00333549141296s408
|View full text |Cite
|
Sign up to set email alerts
|

Media Use and Communication Inequalities in a Public Health Emergency: A Case Study of 2009–2010 Pandemic Influenza a Virus Subtype H1N1

Abstract: Strategic public health communication efforts in public health preparedness and during emergencies should take into account potential communication inequalities and develop campaigns that reach across different social groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 31 publications
2
77
0
Order By: Relevance
“…In terms of outbreak information source, the television and radio were found to be the most utilized among the respondents regardless of socio-demographic factors. Recent studies on outbreak information dissemination had reported traditional media channels to still be the main source of information, with minimal health information exchanged on social media [43][44][45][46]. Our findings are also congruent with the study conducted by Vijaya et al [17] where the authors found that majority of the respondents depended on the television and printed media for timely and accurate information during the SARS outbreak in Singapore.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of outbreak information source, the television and radio were found to be the most utilized among the respondents regardless of socio-demographic factors. Recent studies on outbreak information dissemination had reported traditional media channels to still be the main source of information, with minimal health information exchanged on social media [43][44][45][46]. Our findings are also congruent with the study conducted by Vijaya et al [17] where the authors found that majority of the respondents depended on the television and printed media for timely and accurate information during the SARS outbreak in Singapore.…”
Section: Discussionsupporting
confidence: 90%
“…Previous surveys on the psychological and behavioral responses of emerging infectious diseases were reviewed [7][8][9][10]13,14], and the authors included additional questions related to COVID-19. The structured questionnaire consisted of questions that covered several areas: (1) perceived risk related to COVID-19; (2) efficacy belief on precautionary measures; (3) COVID-19 health risk communication; (4) precautionary behaviors practiced against COVID-19 in the past seven days; and (5) socio-demographic data.…”
Section: Questionnairementioning
confidence: 99%
“…PHEP constitutes a broad range of prevention, mitigation, and recovery activities and emphasizes that such goals cannot be accomplished by the government alone, but must also involve the public [6]. Therefore, engaging the public is one of the most critical elements of PHEP and manifests by heightened risk perceptions [7,8], increased knowledge and awareness about specific threats [7,9], and the implementation of precautionary measures [9][10][11]. Guiding the public to become full and active participants in PHEP is essential to improving resilience and reducing the population's overall vulnerability [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Moriarty et al examine immunization information systems and their utility during pandemic events. 9 Other articles illuminate the social determinants of key system outcomes, such as the factors associated with more effective or comprehensive communication strategies 8 or the institutional factors affecting preparedness planning for at-risk populations. 11 The authors, in addition to exploring systems' design and determining ways in which the systems could be improved or enhanced for future responses, focused on developing models, tools, and other applications to aid in knowledge transfer for real-world outcomes.…”
Section: Advancing Study Designmentioning
confidence: 99%